Earthquakes Hazard and large dams in the Himalaya - Vinod K Gaur; GAUR (Vinod K) Ed (New Delhi Indian National Trust for Art and Cultural Heritage, 1993)
The Himalayan thrust belt has, in historic times, produced some of the largest and most energetic Earthquakes in the world. Four such earthquakes that occurred in the last 100 years, have ruptured over 1200-1400 km of the collision boundary leaving two seismic gaps that are bound to be filled in the future by earthquakes of comparable size. The Himalaya being the source of major River systems of the subcontinent, also provide attractive sites for constructing dams to harness their vast but seasonally varying Water resources as well as associated power. Indeed, several dams have already been constructed in the Himalayan Region and many more are under construction, some in the seismic gaps shown in the diagram. But along with the Benefits that they bring, dams also expose downstream populations to risk in case of a possible failure. Large dams in the Himalaya would particularly enhance this risk, as Ground accelerations in the wake of a major earthquake are expected to exceed that due to gravity as has been conclusively shown to have happened during the great 1897 Assam earthquake. It would, therefore, be prudent to bring to bear a thorough analysis of geological and geophysical evidence available on the design of a dam at a given site and design new potentially revealing investigations that may reduce the uncertainties made in various assumptions on which the dam design is based.
Keywords: Earthquake; Himalaya